Different MAF translocations confer similar prognosis in newly diagnosed multiple myeloma patients. Issue 8 (2nd July 2020) - Goldman-Mazur, Sarah; Jurczyszyn, Artur; Castillo, Jorge J.; Waszczuk-Gajda, Anna; Grząśko, Norbert; Radocha, Jakub; Bittrich, Max; Kortüm, Klaus Martin; Gozzetti, Alessandro; Usnarska-Zubkiewicz, Lidia; Valls, Julio D.; Jayabalan, David S.; et al.
Abstract: The MAF translocations, t(14;16) and t(14;20), are considered as adverse prognostic factors based on few studies with small sample sizes. We report on their prognostic impact in a large group of 254 patients – 223 (87.8%) with t(14;16) and 31 (12.2%) with t(14;20). There were no intergroup differences in survival estimates. Median progression-free survival was 16.6 months for t(14;16) and 24.9 months for t(14;20) ( p  = 0.28). Median overall survival (OS) was 54.0 months and 49.0 months, respectively ( p  = 0.62). Median OS in patients who underwent double autologous stem cell transplantation (ASCT) was 107.0 months versus 60.0 months in patients who received single ASCT ( p  < 0.001). ISS 3 was associated with shorter OS (HR = 1.89; 95% CI 1.24–3.19; p  = 0.005) in Cox analysis. Our study suggests that t(14;20) should be considered as an adverse factor of equal prognostic implication to t(14;16).